Identification and Assessment of the Factors causing Cost Overrun in Housing Projects - A. Madhumitha; Priyadharshini . S; Surya Raj Kumar (International Journal of Urban Design and Development, 2023)
Poor cost performance is a major problem in construction industry, especially in developing countries like India. Statistics reveal that majority of the projects faces the issue of cost overrun. The interrelationship between the causes of cost overrun and stakeholders has not been explored yet. The aim of the research is to minimize the effects of project cost overrun. The objective of the study is to categorize and rank the potential factors causing cost overrun. Further, it tries to provide suggestive framework to mitigate cost overrun which affects the project performance. Based on the expert interview and literature study, a questionnaire survey was framed and the results from the survey were validated through case studies. Nine factors were identified as critical factors causing cost overrun. From the findings, suggestive frameworks were proposed to overcome the issue of construction delay, poor communication and price escalation.
Keywords: Cost overrun; cost estimation; delay; mitigation framework; price escalation; stakeholder’s perspective